Purification method and application of coal-based hard carbon material

By employing a method of first alkalizing followed by mixed acid treatment and online conductivity monitoring, combined with centrifugal dehydration and washing with pure water, a low-ash, low-iron coal-based hard carbon material was successfully prepared. This solved the problem of incomplete purification in existing technologies and achieved efficient and stable purification results.

CN121493947APending Publication Date: 2026-02-10ANHUI JIUTAI NEW MATERIAL TECH CO LTD +1

Patent Information

Application Number
CN202610039171.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-13
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively reduce the ash and iron content in coal-based hard carbon materials, leading to a decline in their electrochemical performance and failing to meet the requirements of high-end energy storage devices. Furthermore, traditional purification methods result in inconsistent product quality between batches.

Method used

A coal-based hard carbon material with low ash and low iron was prepared by using a method of first alkalization followed by mixed acid treatment, combined with a tumbling reaction of a mixture of steam and air, using online conductivity monitoring of the endpoint, and combining centrifugal dehydration and washing with pure water.

Benefits of technology

Significantly reducing ash and iron content improves the purity and consistency of the material, enhances the coulombic efficiency and cycle life of the battery, and meets the requirements of high-end energy storage devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121493947A_ABST
    Figure CN121493947A_ABST
Patent Text Reader

Abstract

The invention provides a purification method and application of a coal-based hard carbon material, belongs to the technical field of lithium / sodium ion battery negative electrode materials, and overcomes the defects that according to an existing purification method, the ash content is lower than 3%, the iron content is lower than 400 ppm, and the requirements are difficult to meet. Turning over the materials and reacting for 3.8-4.2 hours in a boiling state; acidizing: mixing an acid solution, and reacting for 2-8 hours at the temperature of 60-100 DEG C; the mixed acid solution comprises hydrochloric acid with the volume concentration of 10%-30% and hydrofluoric acid with the volume concentration of 0.5%-8%; according to the high-purity coal-based hard carbon material and the preparation method thereof, purification and deep impurity removal can be cooperated, the original coal ash content higher than 8% can be reduced to lower than 1%, and the iron content of the high-purity coal-based hard carbon material is lower than 100 ppm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium / sodium-ion battery anode material technology, and in particular to a method for preparing low-ash coal-based hard carbon material by efficient purification using high-ash raw coal as a precursor, as well as the coal-based hard carbon material prepared by this method, an electrode containing the material, and an energy storage device. Background Technology

[0002] Hard carbon materials are considered to be highly promising anode materials for sodium-ion batteries due to their low cost, wide availability, and structural stability. Coal, especially anthracite and bituminous coal, is one of the ideal precursors for preparing hard carbon because of its highly disordered graphite-like microcrystalline structure.

[0003] However, natural raw coal contains a large amount of inorganic mineral impurities (collectively referred to as "ash"), mainly including oxides or salts of silicon, aluminum, calcium, iron, potassium, sodium, etc. These impurities, especially metallic impurities such as iron, can severely impair the electrochemical performance of the final carbon materials: on the one hand, they occupy active sites between carbon layers, leading to a decrease in reversible capacity; on the other hand, during battery cycling, these impurities catalyze side reactions, consume electrolyte, and deteriorate the stability of the solid electrolyte interphase (SEI), resulting in reduced coulombic efficiency and shortened cycle life. Therefore, reducing the ash content, especially the iron content, of coal-based hard carbon to a level suitable for battery applications is crucial for its commercial application.

[0004] Currently, acid washing or alkaline washing is commonly used to purify carbon materials. However, conventional acid or alkaline washing alone has limited effectiveness for raw coal with complex structures and diverse impurity distribution patterns. It is difficult to stably reduce its ash content to below 3%, and the iron content also fails to meet the stringent requirement of below 400 ppm. Furthermore, traditional purification processes are poorly controlled and rely heavily on manual experience (such as using pH test paper to determine the washing endpoint), resulting in large batch-to-batch fluctuations in product quality, which cannot meet the needs of large-scale, consistent production.

[0005] Therefore, developing a targeted, efficient, and controllable coal-based hard carbon purification method to address the technical bottleneck of high-ash raw coal in high-end energy storage has become an urgent problem to be solved in this field. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a purification method for coal-based hard carbon materials that has high purification efficiency, controllable process, and can significantly reduce the ash and iron content of raw coal.

[0007] Another objective of this invention is to provide a coal-based hard carbon material with low ash and low iron content prepared by the above method.

[0008] Another object of the present invention is to provide an electrode and an energy storage device comprising the above-mentioned coal-based hard carbon material.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] In a first aspect, the present invention provides a method for purifying coal-based hard carbon materials, comprising the following steps:

[0011] S1, Alkalization treatment: Mix raw coal and caustic soda flakes at a mass ratio of 1:(1.3-1.7), place them in a cooking device such as a reaction kettle, add water, and at the same time introduce a mixture of steam and air from the bottom of the device to make the material tumble and heat it to boiling. React in the boiling state for 3.8-4.2 hours.

[0012] S2, Acidification treatment: After the alkaline solution is discharged, a mixed acid solution is added to the cooking equipment such as a reaction vessel, and the mixture is reacted at a temperature of 60°C to 100°C for 2-8 hours; the mixed acid solution contains hydrochloric acid with a volume concentration of 10%-30% and hydrofluoric acid with a volume concentration of 0.5%-8%.

[0013] S3, rinsing: The material after steps S1 and S2 is washed with water until the conductivity of the wash liquid drops below 100 μS / cm, thus obtaining preliminarily purified coal-based carbon material.

[0014] S4, Dehydration and deep washing: The preliminarily purified coal-based carbon material is centrifuged for dehydration, and pure water is introduced for washing during the centrifugation process. The centrifugation time is 1980-2020 seconds, and the material is washed until the pH value is controlled between 5.5 and 7.5.

[0015] S5, Drying: The dehydrated coal-based carbon material is dried to obtain purified coal-based hard carbon material with an ash content of less than 1% and an iron content of less than 100 ppm.

[0016] Preferably, the purity of the caustic soda flakes is not less than 99.9%.

[0017] Preferably, the raw coal is coking coal with an initial ash content higher than 8%.

[0018] Secondly, the present invention provides a coal-based hard carbon material prepared by the method described in any of the above-mentioned methods, wherein the ash content is less than 1% and the iron content is less than 100 ppm.

[0019] Thirdly, the present invention provides an electrode comprising the aforementioned coal-based hard carbon material.

[0020] Fourthly, the present invention provides an energy storage device, which is a sodium-ion battery or a supercapacitor, comprising the electrodes described above.

[0021] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:

[0022] 1. Synergistic Purification for Deep Impurity Removal: This invention employs a synergistic purification route of "strong alkali followed by mixed acid." Alkali treatment effectively dissolves acidic oxides such as aluminosilicates in coal; subsequently, a mixed acid of hydrochloric acid and hydrofluoric acid is used. Hydrochloric acid primarily targets metal oxides such as iron and calcium, while hydrofluoric acid powerfully etches silicon-containing minerals (such as quartz). This sequence and combination systematically removes the vast majority of mineral impurities from raw coal.

[0023] 2. Enhanced mass transfer and improved efficiency: By introducing a mixture of steam and air into the bottom of the cooking equipment, not only is a heat source provided, but more importantly, the airflow continuously tumbles the material in the reactor, creating a dynamic reaction environment. This greatly enhances the mass transfer process between the solid and liquid phases, avoids material agglomeration and reaction dead zones, and ensures sufficient and uniform contact between reagents and impurities, thereby significantly improving the purification reaction rate and efficiency.

[0024] 3. Controllable process and stable quality: For the first time, online conductivity monitoring is introduced into the washing process of coal-based carbon materials. The conductivity of the wash liquid <100 μS / cm is used as an objective and quantitative endpoint criterion, replacing the traditional experience-based pH test paper method. This fundamentally ensures the stability of product purity and batch-to-batch consistency, providing a reliable quality control method for large-scale industrial production.

[0025] 4. Integrated deep washing: Combining centrifugal dehydration with pure water washing, deep washing is performed while achieving solid-liquid separation, further removing soluble ions attached to the surface and micropores of carbon material particles, thus ensuring the purity of the product.

[0026] 5. Excellent product performance: This method can stably purify low-quality raw coal with an initial ash content higher than 8% into high-purity coal-based hard carbon material with an ash content of less than 1% and an iron content of less than 100ppm. This fully meets the purity requirements of high-end energy storage devices such as sodium-ion batteries for anode materials and has extremely high industrial application value. Attached Figure Description

[0027] Figure 1 This is a process flow diagram of the purification method of the present invention. Detailed Implementation

[0028] Combination Figure 1 The present invention will be further described in detail below through specific embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0029] The raw coal used in this invention is coal that has undergone coking treatment at 800-1200℃, with an initial ash content of 10.5% and an iron content of 5500-8000 ppm. The caustic soda has a purity of 99.9%. The hydrochloric acid and hydrofluoric acid are industrial grade. The purified water is deionized water with a resistivity ≥18 MΩ·cm.

[0030] Example 1

[0031] S1, Alkalization Treatment: Weigh 1 kg of coking coal and 1.5 kg of caustic soda flakes, add them to a reactor equipped with a stirrer and steam coil, and add 5 L of purified water. Introduce a mixture of steam and air from the bottom of the reactor, controlling the steam flow to raise the material to boiling point and maintain a gentle boil. The introduction of air ensures thorough agitation of the material. The reaction continues for 4 hours.

[0032] S2, Acidification Treatment: After the reaction is complete, drain the alkaline solution. Add 5L of pre-prepared mixed acid solution (20% hydrochloric acid and 2% hydrofluoric acid by volume) to the reactor, heat to 80℃, and react for 4 hours.

[0033] S3, Rinsing: After the reaction is complete, drain the acid solution. Rinse the material countercurrently with a large amount of pure water, and monitor the conductivity of the rinsing outlet in real time. Stop rinsing when the conductivity drops to 85 μS / cm.

[0034] S4, Dehydration and Deep Washing: Transfer the rinsed wet material to a horizontal centrifuge, continuously circulate pure water for washing during centrifugation, and control the total centrifugation time to 2000 seconds.

[0035] S5, Drying: The dehydrated material is dried in a vacuum oven at 120°C for 12 hours to obtain purified coal-based hard carbon material.

[0036] According to GB / T 212-2008 (the same below), the ash content of this material is 0.7%, and the iron content is 70 ppm, determined by ICP-OES method (the same below).

[0037] Example 2

[0038] S1, Alkalization treatment: The mass ratio of raw coal to caustic soda flakes is 1:1.3, and the remaining steps are the same as in Example 1.

[0039] S2, Acidification treatment: The mixed acid contains 10% hydrochloric acid and 5% hydrofluoric acid by volume. The reaction temperature is 60°C, and the reaction time is 8 hours. The remaining steps are the same as in Example 1.

[0040] S3, rinsing: The conductivity endpoint is controlled at 95 μS / cm. The remaining steps are the same as in Example 1.

[0041] S4, Dehydration and Deep Washing: Centrifugation time is controlled at 1980 seconds. The remaining steps are the same as in Example 1.

[0042] S5, Drying: Same as in Example 1.

[0043] The material was found to have an ash content of 0.85% and an iron content of 85 ppm.

[0044] Example 3

[0045] S1, Alkalization treatment: The mass ratio of raw coal to caustic soda flakes is 1:1.7, and the remaining steps are the same as in Example 1.

[0046] S2, Acidification treatment: The mixed acid contains 30% hydrochloric acid and 0.5% hydrofluoric acid by volume. The reaction temperature is 100°C, and the reaction time is 2 hours. The remaining steps are the same as in Example 1.

[0047] S3, rinsing: The conductivity endpoint is controlled at 75 μS / cm. The remaining steps are the same as in Example 1.

[0048] S4, Dehydration and Deep Washing: Centrifugation time is controlled at 2020 seconds. The remaining steps are the same as in Example 1.

[0049] S5, Drying: Same as in Example 1.

[0050] Tests showed that the material had an ash content of 0.8% and an iron content of 75 ppm.

[0051] Comparative Example 1

[0052] Instead of performing S1 alkalization, the raw coal is directly subjected to S2 acidification (under the same conditions as in Example 1), followed by steps S3, S4, and S5.

[0053] The tested material had an ash content of 1.9% and an iron content of 130 ppm.

[0054] Comparative Example 2

[0055] After the S1 alkalization treatment, the mixed acid of the present invention is not used, but only hydrochloric acid with a volume concentration of 20% is used for acidification treatment (other conditions are the same as in Example 1).

[0056] The material was tested and found to have an ash content of 1.4% and an iron content of 105 ppm.

[0057] Comparative Example 3

[0058] In the S3 rinsing step, instead of using conductivity monitoring, a traditional method is used: pH test paper is used to check the rinsing solution until it reaches neutrality.

[0059] Testing revealed that the ash content of the obtained materials fluctuated significantly (0.85%-1.2%), and the iron content fluctuated within the range of 85-130 ppm, indicating poor batch stability.

[0060] Performance testing

[0061] The coal-based hard carbon materials prepared in Examples 1-3 and Comparative Examples 1-2 were used as the negative electrode active material. They were mixed evenly with the conductive agent acetylene black and the binder polyacrylic acid (PAA) in deionized water at a mass ratio of 8:1:1, and then coated onto copper foil to form the negative electrode of a sodium-ion battery. Using metallic sodium as the counter electrode and 1 M NaClO4 in EC / PC (1:1 vol%) with 5% FEC as the electrolyte, CR2032 coin cells were assembled in an argon-protected glove box.

[0062] The battery performance test results are shown in Table 1 below: Table 1

[0063] As shown in Table 1 above, the coal-based hard carbon material purified by the method of this invention exhibits higher initial coulombic efficiency, higher reversible capacity, and excellent cycle stability in sodium-ion batteries. This is due to its extremely low ash and iron content, which reduces side reactions and forms a more stable SEI film.

[0064] In summary, this invention, through specific process combinations and process control, successfully achieves efficient and deep purification of high-ash raw coal, resulting in products with excellent performance and stable processes, possessing enormous potential for industrial production.

[0065] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for purifying coal-based hard carbon materials, characterized in that, Includes the following steps: S1, Alkalization treatment: Mix raw coal and caustic soda flakes at a mass ratio of 1:(1.3-1.7), place them in a cooking device, add water, and at the same time introduce a mixture of steam and air from the bottom of the device to make the material tumble and heat it to boiling. React in the boiling state for 3.8-4.2 hours. S2, Acidification treatment: After the alkaline solution is discharged, a mixed acid solution is added to the cooking equipment and reacted at a temperature of 60°C to 100°C for 2-8 hours; the mixed acid solution contains hydrochloric acid with a volume concentration of 10%-30% and hydrofluoric acid with a volume concentration of 0.5%-8%. S3, rinsing: The material after steps S1 and S2 is washed with water until the conductivity of the wash liquid drops below 100 μS / cm, thus obtaining preliminarily purified coal-based carbon material. S4, Dehydration and deep washing: The preliminarily purified coal-based carbon material is centrifuged for dehydration, and pure water is introduced for washing during the centrifugation process. The centrifugation time is 1980-2020 seconds, and the material is washed until the pH value is controlled between 5.5 and 7.

5. S5, Drying: The dehydrated coal-based carbon material is dried to obtain purified coal-based hard carbon material with an ash content of less than 1% and an iron content of less than 100 ppm.

2. The purification method according to claim 1, characterized in that, The purity of the caustic soda flakes is not less than 99.9%.

3. The purification method according to claim 1, characterized in that, The raw coal is coking coal with an initial ash content higher than 8%.

4. A coal-based hard carbon material, characterized in that, Prepared by the method of any one of claims 1 to 3, the ash content is less than 1% and the iron content is less than 100 ppm.

5. An electrode, characterized in that, It includes the coal-based hard carbon material as described in claim 4.

6. An energy storage device, which is a sodium-ion battery or a supercapacitor, characterized in that, It includes the electrode as described in claim 5.

Citation Information

Patent Citations

  • Preparation method of high purity graphite

    CN101983917A

  • Operation data acquisition, optimization and analysis system based on coal-series graphite purification system

    CN120340640A

  • Method for removing ash from solid carbonaceous material

    US20210347640A1

Cited By

  • Ash element regulated coal-based hard carbon material, and preparation method and application thereof

    CN122380349A